TREND OF RESEARCH RELATED TO GROUP WORK AMONG ADOLESCENTS IN MALAYSIA AND INDONESIA - Nur Hazirah Tajul Ariffin; Aslina Ahmad (OPTIMA: Journal Of Guidance and Counseling, 2021)
This study was conducted to identify the trend of research related to group work among adolescents in Malaysia and Indonesia from the year 2014 to 2020. The specific objective of this study is to investigate the trend of research related to counselling of adolescent groups in Malaysia and Indonesia based on previous studies. Data was obtained from the Internet such as journals, theses and articles. A number of finalised 126 studies in Malaysia and Indonesia were analyzed using descriptive form of frequency and percentage. The result of the study shows that the quantitative design is most widely used in both countries in studying group work among adolescents and the most dominant target group is school students. This study also identifies the variables of the studies and results show that group counseling, guidance counselling and self concept are the most favourable variables in Malaysian and Indonesian studies.   Among the suggestions given by the previous studies were mostly on the improvement of group modules and intervention. The paper concludes with a discussion on future studies related to group counselling in Malaysia and Indonesia.